Maqâshid al-Sharî‘ah Review of the Implementation of Sharia Franchise at 212 Mart Bandar Lampung, Indonesia - Maulidiana, Lina; Famulia, Ledy (al-'adalah, 2023)
This article aims to analyze the fulfillment of maqâshid al-sharî'ah towards the implementation of sharia franchises at 212 Mart Bandar Lampung. The theory of maqâshid al-sharî'ah is a theory that becomes a benchmark in analyzing a new phenomenon in society which aims to make it relevant to the rules in Islam. The problems in this study include how the indicators are used by franchisors who claim to apply Sharia principles and how to implement franchises that apply Sharia principles when viewed from maqâshid al-sharî'ah. The purpose of the discussion in this study is to determine the fulfillment of maqâshid al-sharî'ah in the 212 Mart Bandar Lampung shari'ah franchise. The research method uses qualitative methods with an empirical juridical approach. The results of the study show that what is implemented by 212 Mart Bandar Lampung has fulfilled the elements of dlarûriyyât, hajiyyât, and tahsîniyyât although there are still things that need to be adjusted to the basic rules for determining ujroh following the DSN MUI Fatwa that applies in Indonesia.